Erythropoietin Improves Atrophy, Bleeding and Cognition in the Newborn Intraventricular Hemorrhage - Hierro-Bujalance, Carmen; Infante-Garcia, Carmen; Sanchez-Sotano, Daniel; del Marco, Angel; Casado-Revuelta, Ana; Mengual-Gonzalez, Carmen Maria; Lucena-Porras, Carmen; Bernal-Martin, Marcos; Benavente-Fernandez, Isabel; Lubian-Lopez, Simon; Garcia-Alloza, Monica (Frontiers in Cell and Developmental Biology, 2020)
The germinal matrix-intraventricular hemorrhage (GM-IVH) is one of the most devastating complications of prematurity. The short- and long-term neurodevelopmental consequences after severe GM-IVH are a major concern for neonatologists. These kids are at high risk of psychomotor alterations and cerebral palsy; however, therapeutic approaches are limited. Erythropoietin (EPO) has been previously used to treat several central nervous system complications due to its role in angiogenesis, neurogenesis and as growth factor. In addition, EPO is regularly used to reduce the number of transfusions in the preterm infant. Moreover, EPO crosses the blood-brain barrier and EPO receptors are expressed in the human brain throughout development. To analyze the role of EPO in the GM-IVH, we have administered intrventricular collagenase (Col) to P7 mice, as a model of GM-IVH of the preterm infant. After EPO treatment, we have characterized our animals in the short (14 days) and the long (70 days) term. In our hands, EPO treatment significantly limited brain atrophy and ventricle enlargement. EPO also restored neuronal density and ameliorated dendritic spine loss. Likewise, inflammation and small vessel bleeding were reduced, resulting in the preservation of learning and memory abilities. Moreover, plasma gelsolin levels, as a feasible peripheral marker of GM-IVH-induced damage recovered after EPO treatment. Altogether, our data support the positive effect of EPO treatment in our preclinical model of GM-IVH, both in the short and the long term.